1997
DOI: 10.5980/jpnjurol1989.88.566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Donor Renal Artery Reconstruction in Kidney Transplantation

Abstract: We conclude that (1) Ligation and imperative surgery tend to be associated with renal infarction, although it does not affect GFR. (2) Renal artery reconstruction was highly successful in preserving renal mass (or normal cortical image), albeit longer ischemic time than simple ligation. (3) Considering importance of preserved nephron mass in clinical renal transplantation every attempt should be made to repair the donor arterial anomalies when expected (elective) or found (imperative). (4) Thorough preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Troppmann et al 17 reported that small, usually upper polar accessory renal arteries could be ligated if they supplied less than 5%-10% of the renal parenchyma. Miura et al 18 described that renal arterial reconstruction is indicated except for arteries with diameters of less than 1 mm and those that supply the upper pole of the kidney. Ganesan et al 19 reported that an upper polar artery could be safely ligated if the surface area supplied by the clamped polar artery is smaller than 1 cm 2 , whereas a lower polar artery should never be ligated because it supplies the ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Troppmann et al 17 reported that small, usually upper polar accessory renal arteries could be ligated if they supplied less than 5%-10% of the renal parenchyma. Miura et al 18 described that renal arterial reconstruction is indicated except for arteries with diameters of less than 1 mm and those that supply the upper pole of the kidney. Ganesan et al 19 reported that an upper polar artery could be safely ligated if the surface area supplied by the clamped polar artery is smaller than 1 cm 2 , whereas a lower polar artery should never be ligated because it supplies the ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these techniques have extended the available treatments for these diseases. Ex vivo repair has also allowed the repair of traumatically damaged donor kidneys, thus increasing the transplant rate 24 . Hence, the benefits of ex vivo surgery and autotransplantation may not be applied only to difficult clinical problems, but also to the field of allotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical and microsurgical techniques of intracorporeal and ex vivo surgeries have been used to implant kidneys with multiple arteries. 5,7,9 The advantages, disadvantages and the outcome of ex vivo and intracorporeal anastomotic techniques are not clearly defi ned up to this moment.1 In situ techniques include the use of various branches of the recipient hypogastric artery, a combination of hypogastric and external iliac arteries, multiple individual endto-side anastomoses to the external iliac artery, and even the inferior epigastric artery 7,10 . On the other hand, the main objective of the ex vivo microvascular techniques 11 is to create a single arterial ostium to facilitate the in situ vascular anastomosis with maximal accuracy and minimal warm ischemic damage to the kidney.…”
Section: Commentsmentioning
confidence: 99%